Disciplinary Intervention for Students through Worship - Dermawan, Oki (Universitas Islam Negeri Raden Intan Lampung, 2018)
Discipline is one part of educational character that needs to be instilled to the children since primary school. Application of discipline could deliver through various activities, such as entering the class and when performing congregational prayers, obey the agreement rules and orderly in line up. The purpose of this study is finding out the discipline at Ar Raudhah elementary school, how to apply discipline to the students and what factors are causes of indiscipline in this school. This study uses a descriptive qualitative research approach with observation, interviews and documentation as data collection techniques. Miles and Huberman model is the data analysis technique, three steps include, namely: data reduction, data presentation and verification. While the validity test of the data uses triangulation with the same source but use a different method. The result shows us that students had consistently carried out the worship in schools such as memorizing prayers, hadiths and verses of the Quran, Dhuha, and Zuhr prayers. However, there are some students still need to be motivated furthermore they don't play when performing worship. The most common factor for indiscipline is whenever parents still think that learning is in the classroom activity, later on some of parents leave their children lately. Here we need parental involvement in instilling discipline of the students. Keywords: Discipline in elementary school, Islamic school, worship discipline